Case report: Overlapping anti-AMPAR encephalitis with anti-IgLON5 disease post herpes simplex virus encephalitis - Sun, Shihui; Ren, Jiafeng; Zhong, Zhao; Ma, Xuxia; Shang, Danqing; Su, Changjun; Zhao, Xianchao (Frontiers in Immunology, 2024)
Autoimmune encephalitis (AE) is the result of an autoimmune process that occurs as a rapidly advancing encephalopathy. Autoimmune encephalitis was commonly linked to the herpes simplex virus 1 (HSV-1) as the most frequently identified virus. The main areas affected by this invasion are temporal lobe, frontal lobe and limbic system. Limbic encephalitis is a highly uncommon occurrence involving Anti-Alpha-Amino-3-Hydroxy-5-Methyl-4-Isoxazolepropionic Acid Receptor (AMPAR) encephalitis and Anti-IgLON family member 5 (IgLON5) disease, both belonging to the rare category. As far as we know, this is the first report that a patient diagnosed with AMPAR encephalitis overlapped with anti-IgLON5 disease post Herpes Simplex Virus Encephalitis (HSE), which helps to broaden the range of this uncommon autoimmune disease. We recommend the autoantibody testing in all patients with HSE, particularly those involving neurological relapses or progression.